2013
DOI: 10.21909/sp.2013.01.622
|View full text |Cite
|
Sign up to set email alerts
|

Serial Position and Distance Effects in Visual Working Memory

Abstract: Numerous studies have identified and explored the factors that affect order information processing in verbal working memory (WM), whereas little is known about order maintenance in visual WM. To gain better insight into the possible mechanisms of representing order in visual WM, we assessed the extent of serial position and item distance effects on visual WM. 20 students performed a visual WM task. They were asked to encode and maintain either the identity or temporal order of four visual stimuli. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Contrary to word lists (Experiment 1), only recency effects were observed for short stories (for similar results with visual stimuli, see Dolenc, Bon, & Repovš, 2013;Hay, Smyth, Hitch, & Horton, 2007). This result is reconcilable with recent findings that suggest that primacy effects in memory are mostly due to rehearsal (e.g., Tan & Ward, 2000).…”
Section: Memorysupporting
confidence: 74%
“…Contrary to word lists (Experiment 1), only recency effects were observed for short stories (for similar results with visual stimuli, see Dolenc, Bon, & Repovš, 2013;Hay, Smyth, Hitch, & Horton, 2007). This result is reconcilable with recent findings that suggest that primacy effects in memory are mostly due to rehearsal (e.g., Tan & Ward, 2000).…”
Section: Memorysupporting
confidence: 74%
“…The fact that we observed a recency bias in our paradigm is interesting. Different studies have reported either recency (Cheadle et al, 2014; Dolenc et al, 2013; Gorgoraptis et al, 2011) or primacy effects (Rangelov & Mattingley, 2020), and some studies have observed both (Hu et al, 2014; Kool et al, 2014). Still other studies have reported no significant biases in temporal integration (Kool et al, 2014; Waskom & Kiani, 2018).…”
Section: Discussionmentioning
confidence: 99%